1996
DOI: 10.1111/j.1365-2133.1996.tb01143.x
|View full text |Cite
|
Sign up to set email alerts
|

COL3A1 mutations cause variable clinical phenotypes including acrogeria and vascular rupture

Abstract: We have recently analysed by histological, protein and molecular DNA techniques 23 mutations of the collagen III gene (COL3A1), most of which cause premature arterial fragility, thin skin and variants of vascular Ehlers-Danlos syndrome. There were 14 glycine substitutions between residues 637 and 1021, eight exon skips between exons 7 and 45 and one small inframe deletion. The glycine substitutions produce a gradient of increasingly abnormal clinical phenotypes from exons 36 to 49 while the clinical severity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
40
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(44 citation statements)
references
References 28 publications
2
40
0
2
Order By: Relevance
“…Genotype–phenotype correlation in patients with vascular EDS is not always clear cut, with intra‐ and inter‐family variability widely recognized. Glycine substitutions which disrupt collagen helix formation are commonly associated with significant vascular risk and an easily recognizable clinical phenotype [Pope et al, ]. Recent reports have correlated the degree of collagen (III) deficiency with age of onset of vascular complications [Shalhub et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Genotype–phenotype correlation in patients with vascular EDS is not always clear cut, with intra‐ and inter‐family variability widely recognized. Glycine substitutions which disrupt collagen helix formation are commonly associated with significant vascular risk and an easily recognizable clinical phenotype [Pope et al, ]. Recent reports have correlated the degree of collagen (III) deficiency with age of onset of vascular complications [Shalhub et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…One candidate gene to be considered is the collagen III gene, as Pope et al [29]found 23 mutations of the collagen III gene (COL3A1) in acrogeria with pronounced vascular rupture. Premature arterial fragility and skin thinning also occur in vascular variants of Ehlers-Danlos syndrome caused by mutations in the COL3A1 gene [29].…”
Section: Discussionmentioning
confidence: 99%
“…Premature arterial fragility and skin thinning also occur in vascular variants of Ehlers-Danlos syndrome caused by mutations in the COL3A1 gene [29]. Especially 3′ mutations of the triple-helical coding region of the COL3A1 gene lead to an acrogeric phenotype with thinning of the skin and capillary telangiectasia, while 5′ or middle helical exon skips are phenotypically discrete [30].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the unique mutation found in the present patient should be considered to be pathogenic. Recent reports indicated that the mutant region of the type III collagen might reflect clinical severity of the phenotype in terms of prognosis [10–13]. There are many reports that the position of the mutation in COL3A1 may play a role in a common natal complication for each family, such as subarachnoid haemorrhage [14], intraperitoneal bleeding [15] or spontaneous perforation of the iliac artery [8].…”
Section: Discussionmentioning
confidence: 99%